Patient, Surgery, and Hospital Related Risk Factors for Surgical Site Infections following Total Hip Arthroplasty - Georgios Triantafyllopoulos; Ottokar Stundner; Stavros Memtsoudis; Lazaros A. Poultsides (The Scientific World Journal)
Surgical site infections (SSI) following total hip arthroplasty (THA) have a significantly adverse impact on patient outcomes and pose a great challenge to the treating surgeon. Therefore, timely recognition of those patients at risk for this complication is very important, as it allows for adopting measures to reduce this risk. This review discusses literature reported risk factors for SSI after THA. These can be classified into patient-related factors (age, gender, obesity, comorbidities, history of infection, primary diagnosis, and socioeconomic profile), surgery-related factors (allogeneic blood transfusion, DVT prophylaxis and coagulopathy, duration of surgery, antibiotic prophylaxis, bearing surface and fixation, bilateral procedures, NNIS index score, and anesthesia type), and hospital-related factors (duration of hospitalization, institution and surgeon volume, and admission from a healthcare facility). All these factors are discussed with respect to potential measures that can be taken to reduce their effect and consequently the overall risk for infection.